1998
DOI: 10.1292/jvms.60.1273
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Survey of Feline Retrovirus Infections in Domestic and Leopard Cats in Northern Vietnam in 1997.

Abstract: ABSTRACT. The prevalence of infections with three feline retroviruses (feline immunodeficiency virus (FIV), feline leukemia virus (FeLV) and feline syncytial virus (FSV)) was examined in northern Vietnam in 1997. We collected a total of 77 blood samples from 69 domestic and 8 leopard cats, and examined the presence of anti-FIV and FSV antibodies and FeLV p27 antigen in the plasma samples by the indirect immunofluorescence and/or two commercial kits. None of the samples was positive for FIV and FeLV. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 19 publications
3
33
0
1
Order By: Relevance
“…The seroprevalence of FFV in German domestic cats was found to be 39%. This result is in accordance with previous studies on the detection of FFV in domestic cats from Vietnam, Australia and Switzerland with 30-80% FFV positive animals depending on age, sex and geographic region ( [Miyazawa et al, 1998], [Winkler et al, 1999], [Nakamura et al, 2000] and [Romen et al, 2006]). …”
Section: Discussionsupporting
confidence: 93%
“…The seroprevalence of FFV in German domestic cats was found to be 39%. This result is in accordance with previous studies on the detection of FFV in domestic cats from Vietnam, Australia and Switzerland with 30-80% FFV positive animals depending on age, sex and geographic region ( [Miyazawa et al, 1998], [Winkler et al, 1999], [Nakamura et al, 2000] and [Romen et al, 2006]). …”
Section: Discussionsupporting
confidence: 93%
“…Serosurveys have not detected FIV antibodies in cheetahs (261), wildcats (87,220), five species of South American felids (119), leopard cats (184,255), civets (184), or sandcats (288), whereas evaluations of wildcats from France (122) and Saudi Arabia (288) demonstrated low levels (Ͻ10%) of FIV seropositivity.…”
Section: Feline Species With Fivmentioning
confidence: 99%
“…There was no significant difference in the infection rates of the viruses between male and female cats. We have reported that the 69 cats were neither infected with feline immunodeficiency virus (FIV) nor feline leukemia virus, although 20 cats (29%) were infected with FSV (12).…”
mentioning
confidence: 99%